Measuring the impact of training: assessment of the ‘Building Bridges through Leadership Training’ program of Bangladesh Youth Leadership Center (BYLC) - Mumu, Sumaiya Noor (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2020.